Animals : Documents for Contemporary Art. - Ramos, Filipa; Agamben, Giorgio; Baker, Steve; Bellour, Raymond; Berger, John; Burt, Jonathan; Chiang, Ted; Chua, Kevin; Critchley, Simon; Deleuze, Gilles; Derrida, Jacques, 1930-2004; Freccero, Carla; et al. (London : Whitechapel Gallery., 2016)
Allora & Calzadilla, Francis Alys, Julieta Aranda, Brandon Ballengee, Lygia Clark, Marcus Coates, Jimme Durham, Marcel Dzama, Simone Forti, Pierre Huyghe, Joan Jonas, Eduardo Kac, Mike Kelley, Robert Morris, Henrik Olesen, Claire Pentecost, Lea Porsager, Carolee Schneemann, Michael Stevenson, Rodel Tapaya, Rosemarie Trockel, Apichatpong Weerasethakul, Haegue Yang, Adam Zaretsky
Contemporary art has emerged as a privileged terrain for exploring interspecies relationships, where diverse topical issues intersect. Observations of empathy among non-humans prompt reconsiderations of the human. Animals nonverbal communication has affinities with poetic expansion of the boundaries of language. And the freedom of animal life in the wild from capitalist structures suggests possible models for reconfiguring society and our relationship to the wider environment. Artists' engagement with animals also opens up new perspectives on the dynamics of dominance, oppression and exclusion, with parallels in human society.
boek